Challenges and Clinical Relevance in Diagnosing Metastatic Cells From Non‐Hematopoietic Malignancies in Bone Marrow Aspirates - Elise Kaspi; Charlotte Grosdidier; Yaël Berda‐Haddad; Maud Arpin; Sylvie Cointe; Shirley Fritz; Amandine Bonifay; Marie Koubi; Carine Jiguet‐Jiglaire; Patrice Roll; Diane Frankel (Cancer Medicine)
ABSTRACT Introduction The causes of cytopenias are numerous, and the bone marrow aspirate helps to identify them. In rare cases, these cytopenias are due to bone marrow metastases from solid cancers. The techniques used in hematology laboratories are limited in characterizing these cells. Interaction with the cytopathology laboratory becomes critical for characterizing tumor cells and completing a comprehensive diagnosis from the bone marrow aspirate. Methods This article describes a series of 38 bone marrow aspirates from 36 patients with bicytopenias who underwent bone marrow aspiration and for whom the hematologists sent the sample to the cytopathology laboratory to complete the diagnosis by immunocytochemistry and FISH if necessary. Results The mean age of patients is 66 years, and the sex ratio is 2.8. Metastases were found in 11 cases of lung carcinoma, 4 cases of prostate carcinoma, 2 cases of breast carcinoma, 1 case of kidney carcinoma, 1 case of glioblastoma, 1 case of Ewing's sarcoma, and 1 case of melanoma. Among them, bone marrow aspiration was the only method to establish the initial diagnosis for seven patients. In six cases, immunocytochemistry confirmed the presence of carcinoma cells but could not identify their origin. In seven cases, tumor cells were insufficient to be characterized by immunocytochemistry. Conclusion Collaboration between laboratories is essential for the management of bone marrow aspirates containing non‐hematopoietic metastases. Bone marrow aspiration may be sufficient to diagnose solid tumors, enabling faster initiation of treatment for patients already at an advanced stage of their disease.